Studies on bacterial exotoxins with special reference to those of the staphylococci and the group of sporing anaerobes - Borthwick, Grizel Rebecca (The University of Edinburgh, 1935)
At an early stage in the development of bacteriological science it was clearly shown that certain micro -organisms were pathogenic by virtue of their diffusible poisons, now designated exotoxins.

The exact definition of exotoxins in the light of recent knowledge has become a matter of great difficulty. Formerly they were characterised according to certain properties, their ready diffusibility in bacterial culture and filtrability from the living organism, thermolability at 65 °C, high toxicity in the animal body after an incubation period following their injection, particularly their selective action on certain tissues and tissue elements and their antitoxinogenic effect. Two toxins, those of B. diptheriae and B. tetani exhibit all these properties. Certain bacterial toxins which may reasonably be classified among the exotoxins differ from these of B. diptheriae and B. tetani in certain important features and the characterisation stated above is therefore too rigid. The most important character in the determination of an exototin is now considered to be the ability to stimulate the production of a specific antitoxin in the animal body. It is suggested that this character may in some measure be shared with the endotoxins. In the absence of any well defined characterisation of exotoxins in general the toxin of each organism must be characterised individually.

This also applies to the elaboration of exotoxins. There is no proof they are invariably a product of bacterial metabolism or are freed on autolysis of the bacterial cell and there is no constant correlation between bacterial growth and toxin production, some toxins, such as that of the classica" B. welchii, being obtained from young actively growing cultures and others, for example that of B. diphtheriae, only from older cultures. It seems probable that the mechanism of toxin production varies with each type of bacterium.

Exotoxins also play parts of widely different importance in the mechanism of infection. Some organisms, such as B. diphtheriae and B. tetani, have low invasive powers and are pathogenic only by virtue of their toxins while in the case of others, for example the'Stáphylococci, the exotoxin is a less dominant feature in the pathogenic mechanism of the organism.

In this thesis special study is made of the exotoxins of Staphylococcal and B. welchii strains. In addition the absorption of these and V. septique toxins from the alimentary tract is considered.